The Assessment of Forced Penetration: A Necessary and Further Step Toward Understanding Men’s Sexual Victimization and Women’s Perpetration - Anderson, RaeAnn E. (Journal of contemporary criminal justice, 2020)
A unique form of sexual victimization that often goes undiscussed and, therefore, underassessed is that of being forced to penetrate another person (i.e., forced penetration). Due to forced penetration being a relatively novel addition to the definition of rape, there is a lack of assessment tools that identify forced penetration cases. Thus, the goal of this study was to assess the utility and validity of new items designed to assess forced penetration. More than 1,000 participants were recruited across three different studies to assess forced penetration victimization and perpetration. The rate of forced penetration victimization ranged from 4.51% to 10.62%. Among men who reported victimization of any type, 33.8% to 58.7% of victimized men reported experiencing forced penetration across the samples, suggesting this experience is common. All new and unique cases of sexual victimization identified by the forced penetration items were those of heterosexual men. These findings suggest that assessing for forced penetration would increase the reported prevalence rates of sexual victimization, particularly in heterosexual men (and correspondingly, rates of perpetration in women).